Avaliação das características histopatológicas e imuno-histoquímicas do fronte de invasão tumoral do carcinoma espinocelular cutâneo de cabeça e pescoço e sua importância no comportamento biológico - Melo, Juliana Carneiro [UNESP] (2013)
The Squamous Cell Carcinoma (SCC) is a malignant epidermal tumor of squamous epithelial cells, characterized for greater aggressiveness much higher incidence of metastasis than Basal Cell Carcinoma (BCC). The deepest invading tumor area, known as invasive tumor front usually disclose less differentiated malignant cells, compared with the whole lesion. Recent studies demonstrate the influence of the invasive tumor front pattern on the prognosis of larynx and uterine cervix SCC. However, there is no studies about that on cutaneuos SCC of the head and neck. To study the clinical, histopathological and immunohistochemical profile of the SCC from head and neck and its invasive tumor front, correlating it with its biological behavior. The study was a retrospective type coorte, where the patients with histopathological diagnosis of head and neck cutaneous SCC among 1999 to 2009 were selected. The evaluation of invasive tumor front was immunohistochemistry for E-cadherin, ki-67 and p53. The pattern of invasive tumor front, as well as E-cadherin and ki-67 expressions, at superficial and deep sites, did not present association with histopathological prognostic criteria. The findings showed that E-cadherin, p53 and Ki-67 were more highly expressed in tumors with size ˃ 2cm. Regarding the thickness of the tumor, we observed that p53 was expressed in depth in thicker lesions (Breslow thickness greater than 2 mm), which was also accompanied by higher expression of Ki-67. p53 expression, at superficial site, had inverse association with thickness criteria (p<0,049) and, at deep site, had direct association with local inflammatory process intensity (p<0,046). The invasive tumor front, as well as E-cadherin, ki-67 and p53 expressions, at superficial and deep sites, did not demonstrate impact on free disease survival. The characteristics of invasive tumor front did not correlate with prognosis in cutaneuos SCC of the head and neck regarding to the ...